Personalized pension projection in Chile: evaluation of its impact in the retirement decision - Miranda Pinto, Jorge (Estudios de Economía, 2013)
This paper evaluates the impact caused by attaching a personalized pension projection (PPP), to the annually report of pension savings. This PPP shows the revenues obtained by the workers when postponing their retirement three years after the legal age for retirement in the Chilean pension system. The method to correct the endogenous treatment which was used it was a quasi-experimental method using instruments such as geographical and demographical information and the number of post offices by Region. The results show that the PPP’s reception once has not significant effect on the retirement decision. However, when the treatment is intensified it begins to be taken into consideration. The PPP’s reception during two consecutive years, 2005 and 2006, significantly reduced the probability of retirement decision during the year 2011. Finally, the results show that the treatment has much more effects in individuals with higher pension savings.